The EffectivenessOf BiorafiaIn Reducing Biological Oxygen Demand (BOD5) Content In The Sail River’s Water - Rizka Novtri Andini; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTOne of the pollutions that enters the Sail River is organic pollutants derived from domestic waste. Efforts to reduce organic pollutants can be conducted by using biocords. Biocord is a rope in the form of three-dimensional fine fiber webbing that is able to hold microorganisms in large quantities. This research used biorafia media (material made from raffia-based materials). The method used was CRD with 3 different biorafia densitieslow density (P1), medium density (P2) and  high density (P3) with 3 replications each. Biorafia is placed in a ditch drained from the Sail River. Biorafia functions as a place attached to microorganisms (biofilms). The degradation process of organic matter occurs when in contact with biofilms that are present in biorafia. The purpose of this study was to reduce the levels of BOD5. The results showed a decrease in BOD5 levels with a time interval of 1 month. The effectiveness of the decrease in the average BOD5 was P1 71,4,%, P2 74,1% dan P3 69,5%. Keywords:biocord, biorafia, organic pollutants, microorganisms